2020
DOI: 10.1111/os.12619
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a Novel 3D‐Printed Patient‐Specific Intramedullary Guide to Control Femoral Component Rotation in Total Knee Arthroplasty

Abstract: Objective: Total knee arthroplasty (TKA) is one of the most universal and effective means for treating terminal stage osteoarthritis (OA) of knee. Accurate intramedullary guide of femur is the basis for the distal femoral cuts. Determining the surgical transepicondylar axis (sTEA) is the key to reconstruction of the femoral rotational alignment, because the correct rotational alignment can place the femoral component in the right position, balance the flexion gap so that the inner and outer tension is equal, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Thus, in our study, we further compared the number of patients with a knee exion angle above 100° in the three groups, and we found that there were more patients in groups C1 and C2 than in the control group on the 7th day and at 3 months after surgery. AKS scoring is a commonly used method to evaluate knee joint function [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in our study, we further compared the number of patients with a knee exion angle above 100° in the three groups, and we found that there were more patients in groups C1 and C2 than in the control group on the 7th day and at 3 months after surgery. AKS scoring is a commonly used method to evaluate knee joint function [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…However, researchers are focused on the design and fabrication of high wear-and tear-resistant biomedical implants to overcome the pain of osteoarthritis (OA) patients (Ref [19][20][21], whereas many researchers presented metal, composite materials fabricated through laser sintering technique using Ti-6Al-4V with nano-cBN/TiO 2 reinforcements (Ref [22][23][24][25][26]. The author reported that on adding nano-cBN/TiO 2 reinforcements, the service life of the implant increased very significantly.…”
Section: Intervertebral Disks and Implantsmentioning
confidence: 99%
“…In addition to this, the investigation can also be carried out on the effects of the shape and size of the reinforced particle in the base powder on the performance of the biomedical components. 88.7 ± 1.5 MPa 1.31 ± 0.2 g/cm 3 Average asperity height: 24.5 μm ----- [22] 101.03MPa Volume fraction: 31%…”
Section: Recommendations For Future Workmentioning
confidence: 99%
“…There are various types of additive manufacturing state-of-the-art and techniques in the design and development of various 3D components [1,2]. Recently, researchers are involved in the design and fabrication of improved biomedical implants used in knee and hip joint replacement for Osteoarthritis (OA) patients [3][4][5]. Osteoarthritis (OA) is a form of degenerative joint pain caused by wear and tear on joints.…”
Section: Introductionmentioning
confidence: 99%